2016
DOI: 10.1097/ijg.0000000000000230
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy in Patients With Glaucoma Over 80 Years of Age

Abstract: The surgical outcomes of trabeculectomy in patients older than 80 years were found to be similar to those of younger controls. Taking into consideration elderly glaucoma patients' general health condition and life expectancy, age alone may not be a barrier to performing glaucoma filtration surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…In this study, glaucoma surgery was not found to be significantly associated with visual performance [21]. Duman F et al compared the surgical outcomes of trabeculectomy performed in patients above 80 years with those of younger controls [2]. After 1 year, the failure rate was 31.3% in the elderly group, which is not significantly different from that of younger patients (p = 0.98) [2].…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…In this study, glaucoma surgery was not found to be significantly associated with visual performance [21]. Duman F et al compared the surgical outcomes of trabeculectomy performed in patients above 80 years with those of younger controls [2]. After 1 year, the failure rate was 31.3% in the elderly group, which is not significantly different from that of younger patients (p = 0.98) [2].…”
Section: Discussionmentioning
confidence: 53%
“…Glaucoma is an important problem for elderly patients' social lives [2,16]. Reading, walking, and eating can sometimes be difficult for glaucoma patients [2,16]. Visual field (VF) defects are particularly important for progressive disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations